The Effect of No-Shearing Treatment on the Growth of Eucalyptus Seedlings (Eucalyptus pellita F. Muell) - Harahap, Alex Andriadi; Qomar, Nurul; Hapsoh, Hapsoh (Jurnal Biologi Tropis, 2026)
Leaf pruning is often used to suppress transpiration, but experimental evidence in Eucalyptus suggests that reducing leaf area is not always necessary and can reduce seedling performance. This study aimed to evaluate the effect of leaf pruning on the survival and early vegetative growth during the seedling phase of Eucalyptus pellita F. Muell. This study used an experimental approach, using a completely randomized design (CRD) with 4 treatments and 5 replications. The results showed that the effect of leaf pruning on the growth of Eucalyptus pellita seedlings resulted in good average growth in vegetative growth parameters, such as normal plant life at 21 days after planting (DAP), plant height, stem diameter, number of leaves, seedling recovery rate, and root volume. This indicates that the presence of intact leaves plays an important role in supporting the process of photosynthesis, carbohydrate accumulation, and distribution of assimilates to growth organs, thereby increasing seedling vigor. On the other hand, root length and root dry weight did not show any significant effect, due to the presence of a root growth limiting factor, namely the tube, so that the roots could not grow to their maximum length (the roots only surrounded the tube position). The conclusion is that there is an effect of the treatment without leaf shears on the survival success and initial vegetative growth during the nursery phase of Eucalyptus pellita F. Muell.